2015
DOI: 10.1098/rspb.2014.2480
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of information: social transmission dynamics within groups of non-social insects

Abstract: While many studies focus on how animals use public information, the dynamics of information spread and maintenance within groups, i.e. the 'ecology of information', have received little attention. Here we use fruitflies trained to lay eggs on specific substrates to implement information into groups containing both trained and untrained individuals. We quantify inter-individual interactions and then measure the spread of oviposition preference with behavioural tests. Untrained individuals increase their interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…Recent studies have shown that flies tend to show increased movement coordination and aggregation as a function of density and social encounters [35,36]. We previously found that the presence of informed flies within a group increases the number of interactions [21]. These interactions may potentially induce behavioural changes in uninformed flies, which become more gregarious even in the absence of informed peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that flies tend to show increased movement coordination and aggregation as a function of density and social encounters [35,36]. We previously found that the presence of informed flies within a group increases the number of interactions [21]. These interactions may potentially induce behavioural changes in uninformed flies, which become more gregarious even in the absence of informed peers.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we defined an interaction between two individuals based on spatial and temporal constraints [21]: (i) proximity between two flies had to be smaller than 1.1 average fly body lengths and (ii) the duration of the contact had to be at least five time frames (0.5 s; figure 2). Moreover, to discriminate between the initiator and receiver of each interaction, we calculated the mean speed of the individuals over the four time frames that preceded each interaction.…”
Section: (B) Data Preparationmentioning
confidence: 99%
“…Adults acquire social information for selecting mating partners (Mery et al, 2009) and oviposition sites (Battesti et al, 2012(Battesti et al, , 2015Sarin and Dukas, 2009), while also vectoring yeast communities that are beneficial for the development of future larvae (Durisko and Dukas, 2013;Stamps et al, 2012;Wertheim et al, 2002). Larvae collectively alter the foraging substrate, which may facilitate burrowing for nutrient acquisition and predator avoidance Reaume and Sokolowski, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fruits also serve as primary habitat and source of nutrients for the developing larvae (Wertheim et al, 2005), thereby creating considerable potential for social interactions. Laboratory studies in which the composition and size of D. melanogaster groups could be manipulated have begun to reveal the rich social repertoire of adults and larvae, highlighting many similarities with socially more complex animals, such as the ability to recognize familiar conspecifics (Lizé et al, 2014), establish dominance relationships (Yurkovic et al, 2006), develop stable social interaction networks (Schneider et al, 2012) or copy the food and mate choices of more experienced individuals (Battesti et al, 2012(Battesti et al, , 2015Mery et al, 2009). However, despite the growing interest in the social biology of D. melanogaster, collective dynamics by which groups initially form and disperse on food resources have received little attention (see Prokopy and Roitberg, 2001;Wertheim et al, 2005 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In insects, social learning has been unambiguously demonstrated in social Hymenoptera but this probably reflects limited research effort and recent evidence show that even non-eusocial insects such as Drosophila, cockroaches, and crickets can copy the behavior of others (Battesti et al, 2012, 2015; Waters and Fewell, 2012). In this way, Pasquaretta et al also used the RSiena package to analyze the dynamic of the interaction network of the fruit fly Drosophila melanogaster during social learning experiments.…”
mentioning
confidence: 99%